2017
DOI: 10.1111/iju.13372
|View full text |Cite
|
Sign up to set email alerts
|

Therapies for castration‐resistant prostate cancer in a new era: The indication of vintage hormonal therapy, chemotherapy and the new medicines

Abstract: Abbreviations & Acronyms AIPC = androgenindependent prostate cancer AR = androgen receptor AR-V7 = androgen receptor splice variant 7 BSC = best supportive care BSI = Bone Scan Index CAB = combined androgen blockade CRPC = castration-resistant prostate cancer HHSPC = hormonehypersensitive prostate cancer PFS = progression-free survival PSA = prostate-specific antigen Ra-223 = radium-223 Abstract: When advanced prostate cancer recurred during hormonal therapy and became the castration-resistant prostate cancer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 66 publications
(137 reference statements)
0
13
1
Order By: Relevance
“…Chemotherapy options for castrate-resistant prostate cancer include cabiztaxel, docetaxel, mitoxantrone, and estramustine. 50 Changes specific to these agents are best described in clinical trials involving neoadjuvant treatment before prostatectomy in the absence of the confounding influence of prior ADT or RT. O'Brien et al 51 described treatment-induced histopathologic changes in 50 high-risk prostate cancer patients treated with pre-prostatectomy docetaxel and mitoxantrone.…”
Section: Chemotherapy and Immune Therapymentioning
confidence: 99%
“…Chemotherapy options for castrate-resistant prostate cancer include cabiztaxel, docetaxel, mitoxantrone, and estramustine. 50 Changes specific to these agents are best described in clinical trials involving neoadjuvant treatment before prostatectomy in the absence of the confounding influence of prior ADT or RT. O'Brien et al 51 described treatment-induced histopathologic changes in 50 high-risk prostate cancer patients treated with pre-prostatectomy docetaxel and mitoxantrone.…”
Section: Chemotherapy and Immune Therapymentioning
confidence: 99%
“…For drug selection, drug sensitivity is critical for preventing survival and drug resistance of cancer cells. Although the development of molecular targeted drugs has become popular in many diseases, DNA replication‐inhibiting drugs such as fluorouracil and platinum‐containing drugs are commonly used for aggressive PCa and CRC in which intolerable side‐effects are serious problems . Thus, the identification of novel therapeutic targets to enhance drug sensitivity is required for the development of efficacious strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the development of molecular targeted drugs has become popular in many diseases, DNA replication-inhibiting drugs such as fluorouracil and platinum-containing drugs are commonly used for aggressive PCa and CRC in which intolerable side-effects are serious problems. (1,2,24,25) Thus, the identification of novel therapeutic targets to enhance drug sensitivity is required for the development of efficacious strategies. In this study, we found that ZIC5 positively regulated the proliferation, migration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2008, chemotherapy with docetaxel was the main treatment option for patients with CRPC. More recently, several new treatment options were introduced, including the androgen signaling inhibitors enzalutamide and abiraterone, radium-223, and the new taxane, cabazitaxel [6,7]. These four drugs are now recommended for the treatment of CRPC in several guidelines for PC [8].…”
Section: Introductionmentioning
confidence: 99%